Method of Reducing Air Pollution from Motor Vehicles - Unggul Punjung Juswono; Siti Jazimah Iswarin; Achmad F.D Romly; Rurini Retnowati (Natural B, Journal of Health and Environmental Sciences, 2011)
Increasing of air pollutions which are occurred in Indonesia is running together with the increase of motor vehicle populations. The old motor vehicles contribute to the increase of air pollution significantly due to the imperfectly burning process in their machine. Air pollution is seriously threat human being not only disturb human health but also cause greenhouse effect and global warming. It needs do some research to decrease air pollution caused by motor vehicle to get a better environment. The research has been done by filtration of disposal gas from motor vehicles using water, lubricant and carbonic acid as a filter. The disposal gas from a motor vehicle was flowed throw bottles contain of water, lubricant and carbonic acid. The result showed that water filter can decrease the disposal gas CO and CO2. Oil filter significantly decreased HC gas and carbonic acid filter could be used to decrease Pb.